Synthesis and Reactions of Some New Substituted Benzoxazin-4-One and Quinazolin-4-One - Ziaty, A.K. El-; Shaban, M. E.; Youssef, A. M.; Aasar, N. K. El- (Biological Sciences - PJSIR, 2008)
The reaction of 3,4-dichlorobenzoyl chloride with 3,5-dibromo anthranilic acid yielded benzoxazine deriva- tive (1), whose reaction with primary and secondary amines such as benzyl amine, p-chloroaniline, p-anisidine, p-toluidine, piperidine and morpholine in boiling ethanol yielded six (3,5-dibromo-2-(3,4-dichlorobenzoylamino)- N-substituted benzamides (2-7). Reaction of the derivative (1) with hydrazine hydrate (1:1 molar proportions) gave the unexpected product 6,8-dibromo-2-(3,4-dichlorophenyl)-3-(2-(3,4-dichlorobenzoylamino)-3,5-dibromobenzamido) quinazolin-4-one (8).